Knowledge, Attitude and Practice of Measuring Devices of Oral Liquid Medications in the Population of District East Karachi, Pakistan - Khan, Faiz Ullah; Rehman, Asim Ur; Rashid, Haroon; Khan, Zahid; Rabbi, Fazal; Shah, Syed Mujahid (Journal of Pharmacy Practice and Community Medicine)
Background: Most of the people have poor knowledge and inability to administer liquid medications properly which can lead to medication errors and poor health outcomes as laymen and even health care professionals hardly know about the differences among teaspoon (5ml), tablespoon (15ml) and other measuring devices which have great differences in volumes. Objective: To assess knowledge attitude and practice of measuring devices in the population of district east (Gulshan Iqbal and Jamshed Town) Karachi. Methods: A descriptive survey was conducted and total 98 participants were interviewed and information’s were collected on designed questionnaires proforma. Results: In current results cough syrup were used (74.40%), antacids (12.24%) and (20.40%) multivitamins syrups with different measuring measuring devices such as teaspoons (61.22%), table spoons (33.67%) and other oral cups, syringes and dropper (7.14%) and (25.51%) people had experienced with wrong doses and suffered from ADR’s. Conclusion: Awareness and consciousness about appropriate dosing is important in the use of oral liquid medication, the current study was planned to examine the dosing accurateness of measuring devices used for liquid oral medications above an extensive series of dosing volumes.
Keywords: ADR’s; Teaspoons; Tablespoons; Pharmacist; Pakistan